2009
DOI: 10.1002/ijc.24609
|View full text |Cite
|
Sign up to set email alerts
|

Repeated measures of serum glucose and insulin in relation to postmenopausal breast cancer

Abstract: Experimental and epidemiological evidence suggests that circulating glucose and insulin may play a role in breast carcinogenesis. However, few cohort studies have examined breast cancer risk in association with glucose and insulin levels, and studies to date have had only baseline measurements of exposure. We conducted a longitudinal study of postmenopausal breast cancer risk using the 6% random sample of women in the Women's Health Initiative clinical trials whose fasting blood samples, provided at baseline a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
123
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 132 publications
(131 citation statements)
references
References 31 publications
8
123
0
Order By: Relevance
“…As regards breast cancer, the potential of insulin to contribute to tumor progression has been highlighted in diverse investigations (Rose & Vona-Davis 2012, Sieri et al 2012, Catsburg et al 2014. Nicely supporting these data, in postmenopausal women within the framework of the Women's Health Initiative Observational Study (WHI-OS), the highest tertile of baseline insulin was associated with a twofold risk increase in breast cancer compared with the lowest tertile (Kabat et al 2009). Estrogens perform a fundamental role in hormone-sensitive breast cancer, mainly activating the classical ERs (Hall et al 2001).…”
Section: Discussionmentioning
confidence: 93%
“…As regards breast cancer, the potential of insulin to contribute to tumor progression has been highlighted in diverse investigations (Rose & Vona-Davis 2012, Sieri et al 2012, Catsburg et al 2014. Nicely supporting these data, in postmenopausal women within the framework of the Women's Health Initiative Observational Study (WHI-OS), the highest tertile of baseline insulin was associated with a twofold risk increase in breast cancer compared with the lowest tertile (Kabat et al 2009). Estrogens perform a fundamental role in hormone-sensitive breast cancer, mainly activating the classical ERs (Hall et al 2001).…”
Section: Discussionmentioning
confidence: 93%
“…In our study, we were not able to find any statistically significant associations between either the Mediterranean diet score or the WHO HDI and risk of breast cancer. There is some evidence that a Mediterranean diet could impact on diabetes incidence rates (Martinez-Gonzalez et al, 2008), a disease which is likely on the causal pathway for chronic heart disease, but potentially also for breast cancer (Kabat et al, 2009). A recent analysis of the 14 807 women in the Greek EPIC cohort also found no overall association with the Mediterranean diet score and risk of developing breast cancer, however they did find a marginally significant inverse association among postmenopausal women (Trichopoulou et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Among five studies providing data, two [26,27] found a direct relationship and three [28 -30] found no consistent association between fasting insulin and breast cancer risk in postmenopausal women. Further, in the WHI 6% random sample of women with a baseline measurement for glucose and insulin, the RR for the highest tertile of insulin was about 2, but this was based on only 190 cases of breast cancer, of which only 75 were invasive [31]. Furthermore, there was no consistent evidence of an association between plasma levels of IGF-1 and breast cancer.…”
Section: Diabetes and Breast Cancer Riskmentioning
confidence: 93%